Superiority of allo-SCT to auto-SCT in high-risk T-cell lymphoblastic lymphoma/leukemia patients with aaIPI ≥3: insights from a retrospective, multicenter analysis - Xiaodan Luo; Zhiping Fan; Runhui Zheng; Fen Huang; Na Xu; Pengfei Qin; Jingren Lin; Chunyan Wang; Huiqiang Huang; Huo Tan; Qifa Liu (Blood Science)
High recurrence is a major challenge in treating T-lymphoblastic lymphoma (T-LBL). Allogeneic (allo-) or autologous (auto-) stem cell transplantation (SCT) is recommended to reduce relapse, though the optimal choice remains unclear. This study retrospectively analyzed outcomes in T-LBL patients undergoing SCT, with 44 patients receiving allo-SCT and 25 receiving auto-SCT. After a median follow-up of 115 months, the 5-year cumulative incidence of relapse (CIR) was 30.4% overall, 28.7% for allo-SCT, and 37.7% for auto-SCT (p = 0.660). Five-year overall survival (OS) was 68.2% for allo-SCT and 64.0% for auto-SCT; progression-free survival (PFS) was 68.2% and 64.0%, respectively (p = 0.580, 0.940). Patients with age-adjusted international prognostic index (aaIPI) ≥3 had a significantly higher relapse rate in the auto-SCT group (p = 0.022). Univariate analysis identified male sex, aaIPI ≥3, non-CR at cycle 4, and non-CR1 at SCT as adverse prognostic factors. Allo-SCT may benefit patients with high aaIPI.